Pre-service teacher satisfaction in an emergency (nCOV-19) remote learning environment at volta zone-Ghana - Kumah , Maxwell Seyram; Lokpo, Cephase (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
Emergency remote learning has become necessary due to the nCovid-19 pandemic. This learning method is a system where teaching and learning are done virtually using the internet. The study explored the satisfaction of pre-service teachers in an emergency remote teaching and learning (ERTL) environment. The study investigated the satisfaction level of student teachers in an ERTL environment during the Covid-19 pandemic. Out of the 2000 population of pre-service teachers, a sample of 372 was sampled were purposively and randomly selected. A quantitative method research survey design was used. The instrument was validated using face and content validity and a reliability index of 0.77 was obtained. The findings of the study revealed that the majority (76.68%) of the participants own either a laptop, smartphone, or computer device for their studies. To measure the satisfaction level for feedback, it was observed that 151 were satisfied, 91 were not satisfied and 120 were neutral in their decision. For organization we have 114 were satisfied, 113 were dissatisfied and 144 were neutral. Finally, for personalized learning 154 participants were satisfied, 79 were unsatisfied and 136 neutral. The result from simple regression and correlation indicates that student-tutor interaction and content satisfaction but not sex and digital utilization plays a significant role in the teaching and learning process regarding ERTL. In addition, participants gave reasons for the barriers in the use of ERTL which made it not satisfactory: for instance, access to digital devices but network problems, (b) don’t have money for data (bundle), and technical difficulty. The study concluded that there should be intensified workshops for both tutors and students to use the ERTL system effectively.